DOI: 10.11606/d.7.2016.tde-11012016-133619
|View full text |Cite
|
Sign up to set email alerts
|

Força muscular perineal e incontinência urinária e anal em mulheres após o parto: estudo transversal

Abstract: DEDICATÓRIA Dedico esta dissertação à minha amada mãe, que nunca mediu esforços para proporcionar a mim e aos meus irmãos estrutura para alcançarmos nossos objetivos. Devo a você todas as minhas conquistas. AGRADECIMENTOS RESUMO Introdução:A gravidez e o parto são frequentemente associados à redução da força dos músculos do assoalho pélvico (FMAP) e à incontinência urinária (IU) e anal (IA), devido às alterações que ocasionam nos mecanismos de controle e suporte das estruturas do assoalho pélvico. Objetivos: O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
1
4

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 51 publications
0
1
1
4
Order By: Relevance
“…14 Several factors contribute to fecal incontinence, such as age, overweight, depression, chronic diarrhea and urinary incontinence. 10 However, in the present study, most reported no specific reason for the onset of symptoms.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…14 Several factors contribute to fecal incontinence, such as age, overweight, depression, chronic diarrhea and urinary incontinence. 10 However, in the present study, most reported no specific reason for the onset of symptoms.…”
Section: Discussioncontrasting
confidence: 72%
“…The latter consists of a study that allows the measurement of resting and contraction pressures, the size of the anal canal, the synchronization of sensory and motor components of this channel, as well as the recto-anal capacity, compliance and inhibitory reflex. 10,11 The treatment for fecal incontinence can be conservative or surgical, and even the combination of both. The conservative treatment, when indicated, involves the multidisciplinary team with dietary and pharmacological actions, psychological support, and physical therapy through resources for awareness and strengthening of the pelvic floor muscles.…”
Section: Introductionmentioning
confidence: 99%
“…A população brasileira hoje é aproximadamente de cento e noventa milhões de habitantes, sendo 56% mulheres e destas um terço são acometidas pela IU. Estima-se atingir de 14% a 57% de mulheres com idade entre 20 e 89 anos 1,3 . O sexo feminino é o mais atingido pela incontinência urinaria devido à deficiência de estrogênio, considerando seu papel importante no suporte da pelve e controle da síntese e degradação do colágeno.…”
Section: Artigo Originalunclassified
“…A pesquisa de Zizzi et al (13) , apesar de trabalhar com as variáveis de FMAP e IU evidenciou que as chances da mulher desenvolver IU após o parto foram 20 vezes maiores entre as mulheres que a apresentaram durante a gestação (13) .…”
Section: Discussão Força Muscular Do Assoalho Pélvico Na Prevenção Da...unclassified